A LEARNING OF NEW ZEALAND: A STEP TOWARD GOOD GOVERNANCE FOR INDONESIA - Indra Bastian (Jurnal Akuntansi dan Auditing Indonesia, 2011)
A number of public finance management reforms over the last several decades have served to improve governance in Indonesia. In too many cases, however, reform measures have failed to realize their full potential. Certainly the need for fundamental change was widely accepted. Indonesia has been examining major public finance reform initiatives in a number of jurisdictions that are relevant to Indonesia, with a view to fostering improvements in governance. Our examination of reforms in New Zealand encompassed an extensive review of the literatures. From the New Zealand's experience, it will be an input for implementing good governance in Indonesia.Keywords: New Zealand, Good Governance, Benchmark